Asia Pacific in the Age of Globalization
XIV, 273 p.
Keywords: The essays in this volume examine United States-East Asian relations in the framework of global history, incorporating fresh insights that have been offered by scholars on such topics as globalization, human rights, historical memory, and trans-cultural relations.